Pengaruh Pembagian Jasa Pelayanan Jaminan Kesehatan Nasional dan Motivasi Terhadap Kepuasan Kerja dan Kinerja Pegawai - Bagus Raka Suardana, Ida; Kadek Budi Martini, Luh (RELASI : JURNAL EKONOMI, 2024)
The distribution of national health insurance services has an effect on employee satisfaction and performance The purpose of this study is to determine the effect of service sharing, motivation and job satisfaction on employee performance. The design of this research is quantitative, is the relationship of causality between variables. The study was conducted at community Health centers Karangasem. Data collection techniques used questionnaires to 175 employees. Data were analyzed by data analysis technique Structure Equation Modeling (SEM) program. The results showed there was a significant positive influence between the division of services to job satisfaction. This means that when the division of services increased, employee job satisfaction also increased significantly. There is a pattern of positive influence of motivation on job satisfaction. This means that if the motivation increases then the performance of employees also increased significantly. There is a significant positive influence between the distribution of services to the performance of employees. This means that when the division of services increased, the performance of employees also increased significantly. There is a pattern of positive influence of motivation on employee performance. This means that if the motivation increases then the performance of employees also increased significantly. There is a positive and significant influence between job satisfaction on employee performance. This means that if job satisfaction increases then the performance of employees also increased significantly.